2005
DOI: 10.1016/j.lfs.2005.05.012
|View full text |Cite
|
Sign up to set email alerts
|

The search for the palmitoylethanolamide receptor

Abstract: Palmitoylethanolamide (PEA), the naturally occurring amide of ethanolamine and palmitic acid, is an endogenous lipid that modulates pain and inflammation. Although the anti-inflammatory effects of PEA were first characterized nearly 50 years ago, the identity of the receptor mediating these actions has long remained elusive. We recently identified the ligand-activated transcription factor, peroxisome proliferator-activated receptor-alpha (PPAR-a), as the receptor mediating the anti-inflammatory actions of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
203
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 238 publications
(207 citation statements)
references
References 82 publications
4
203
0
Order By: Relevance
“…1a). URB597 also increased hippocampal levels of the noncannabinoid fatty-acid ethanolamide palmitoylethanolamide (PEA) (26,27) while causing no acute or persistent increase in 2-AG content ( Fig. 1b; see also Table 1, which is published as supporting information on the PNAS web site).…”
Section: Resultsmentioning
confidence: 98%
“…1a). URB597 also increased hippocampal levels of the noncannabinoid fatty-acid ethanolamide palmitoylethanolamide (PEA) (26,27) while causing no acute or persistent increase in 2-AG content ( Fig. 1b; see also Table 1, which is published as supporting information on the PNAS web site).…”
Section: Resultsmentioning
confidence: 98%
“…N-Palmitoylethanolamine has anti-inflammatory (13)(14)(15), anti-nociceptive (16,17), immunosuppressive (18), neuroprotective (19), and antioxidant (20) effects. Recently, it was shown that the anti-inflammatory action of N-palmitoylethanolamine could be mediated by the activation of peroxisome proliferator-activated receptor-␣ (PPAR-␣) (21). Furthermore, N-oleoylethanolamine was shown to be anorexic via PPAR-␣ (22,23) and N-stearoylethanolamine to be pro-apoptotic (24) and anorexic (25).…”
mentioning
confidence: 99%
“…For dogs and cats, the veterinarian-recommended, readymade hemp based supplement Canna-Pet is presently available (containing non-psychoactive cannabidiol). PEA can at present be used to restore skin reactivity in animals in a veterinary medication sold under the trade name Redonyl (LoVerme et al 2005). It is therefore not surprising that owners of animals are also exhibiting increasing interest in the possible use of cannabinoids/medical marijuana in veterinary medicine as can be seen by the number of internet forums concerned with this issue (e.g.…”
Section: Prospective Veterinary Use Of Cannabinoidsmentioning
confidence: 99%